2010
DOI: 10.1007/s00330-010-2008-z
|View full text |Cite
|
Sign up to set email alerts
|

Intra-individual, randomised comparison of the MRI contrast agents gadobutrol and gadoterate in imaging the distal lower limb of patients with known or suspected osteomyelitis, evaluated in an off-site blinded read

Abstract: Imaging of the distal lower limb in this special patient population requires a large number of patients to obtain enough comparative images where non-contrast-agent-dependent factors do not disturb contrast agent efficacy. The ITT analysis showed at least non-inferiority of gadobutrol in comparison to gadoterate. The avoidance of imaging artefacts demonstrates a better outcome for gadobutrol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…The results presented here support previous findings where gadobutrol 1.0 M combined contrastenhanced MRI was effective for the detection and visualization of CNS lesions (12,15,16), as well as lesions elsewhere in the body (5,18,20,21,(23)(24)(25)(26)(27)(28).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results presented here support previous findings where gadobutrol 1.0 M combined contrastenhanced MRI was effective for the detection and visualization of CNS lesions (12,15,16), as well as lesions elsewhere in the body (5,18,20,21,(23)(24)(25)(26)(27)(28).…”
Section: Discussionsupporting
confidence: 90%
“…The efficacy of gadobutrol in MRI of the central nervous system (CNS), together with its physicochemical properties and safety profile, have been extensively studied . Moreover, further studies have shown that gadobutrol 1.0 M is also effective in the MRI of other body regions, including prostate carcinomas , MR angiography , limb osteomyelitis , liver , breast , cardiac tissue , and the kidney .…”
mentioning
confidence: 99%
“…Regarding enhancement characteristics, only the study on hepatocellular carcinoma using a double dose of gadobutrol showed superiority of the 1.0 M GBCA in terms of SNR and CNR (16). The other studies either did not measure SNR or CNR (14,15), or showed equivalence between the two products (18).…”
Section: Resultsmentioning
confidence: 99%
“…1). Seven studies dealt with magnetic resonance angiography (MRA) (410), three with cardiac MRI (1113), six with soft tissue neoplastic and inflammatory lesion (STL) MRI (14–19), and five with central nervous system (CNS) MRI (2024). All studies were published between March 2005 and July 2013 and are representative of the clinical practice in CE-MRI.…”
Section: Methodsmentioning
confidence: 99%
“…In this phase, HC-GBCAs do not provide superior enhancement compared with C-GBCAs at an equivalent dose of 0.1 mmol/kg body weight [ 38 ] . No comparisons have been made between HR-GBCA and C-GBCA or HC-GBCA.…”
Section: Clinical Applicationsmentioning
confidence: 99%